Analysis of Adaptive Behavior of Coastal Communities in Facing Climate Change Through Case Studies in the North Coast of Java - Desmon, Sherly Angguna (Talenta Publisher, 2025)
Now and for the future, the most vital issue that has emerged as an obstacle for human beings around the globe is global climate change. This is characterised by an increase in average global temperatures, increased occurrence of extreme weather conditions and more so an increase in the level of the ocean. The above impacts are alarming, especially on coastal regions as analyzed by Press (2023) where sea level rise affects coastal structure and habitats and the java north coast which is under threat by these natural forces. Indonesia has thousands of kilometer of the coastline and mainly affected with climate change impacts especially the Java northern region. Communities in the coastal areas are feeling the impacts most where impacts range from erosion of sandy beaches, intrusion of salt water into freshwater sources, tidal inundation and shifts in ecosystems with consequences on livelihoods. This research deals with understanding how these coastal communities have adjusted or responded to such changes. Employing systematic integrated review methodology, this research aims at articulating and making sense of available academic data that outlines how these communities are coping through shifts in agricultural practices, enhanced housing structures, and development of other economic opportunities. Using behaviorism theory by B.F.Skinner, the paper depicts a scientific understanding of how adaptive behaviors are maintained. The results will be useful in advising local policymakers as to the most effective strategies for improving the resilience of communities to climate change. Keyword: Adaptive, Coastal, Qualitative, Behavioral Theory